A Study on Reutilization of Waste Plastics Mixed with Sludge Ash - Park, Sang Sook; Araki, Hiroyuki (Journal of the Japan Society of Waste Management Experts, 1997)
The physical and mechanical properties of regenerated LDPE mixed with sludge ash were investigated to evaluate the reutilization feasibility for construction materials. As a result, the physical properties of regenerated plastics get elevated by the ash particles dispersed well to be acted as nuclei, at an ash content ratio of 20%. However, at the content ratio higher than 20%, the physical properties declined because of gathered ash particles. Especially, as the content ratio increases to 40 or 50%, a number of cracks, holes, and lumps of crystalline polymer were found in the SEM photographs. This causes the decline of physical properties and an increase in water absorption rate. The maximum values of compressive-, tensile-, and bending-strength were obtained by adding ash with a content ratio of 20% to 30%. Compared with the standard design strength of ordinary concrete, it was ascertained that a regenerated LDPE mixed with an inorganic ash filler could be used for construction materials.